Decision selection technic for building strengthening methods - Okakpu, Anthony; Özay, Giray (Building and Housing Research Center (BHRC), 2015)
Nowadays, old existing buildings with less load carrying capacity are usually strengthened by the application of a suitable strengthening method. Such methods include the use of steel bracing, FRP jacketing or wrap, concrete jacketing, steel plating, shear wall and hybrid methods. However, there are the possibilities of selecting a strengthening method without comparing for the most efficient method, due to time constraint or little knowledge about strengthening methods. These will however, lead to ignoring the differences among the strengthening methods. In the present study, information about strengthening methods is highlighted as obtained from the survey. According to this information, decision selection program is set up, where different strengthening methods are encoded with their characteristics of solving problems. A case study is applied herewith to check the efficiency of the decision selection program. The recommended strengthening methods are ascertained to be relatively more economical, efficient and time saving.
Keywords: Choice selection; Global strategy; Local strategy; Strengthening